2012
DOI: 10.1016/j.jcgg.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance in Parkinson disease

Abstract: a b s t r a c tSleep disturbance is common in patients with Parkinson disease (PD), but it is often undetected due to inadequate history taking and poor self-reporting. Impaired sleep can have a severe impact on health, general well being, and quality of life. Sleep problems in PD have many potential causes, including the direct effect of PD itself, adverse events of anti-Parkinsonian medications, daytime sleep disturbance, age related causes, and other comorbidities. Patients with PD and their sleep partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…As previously noted, evidence-based sleep interventions are currently lacking for PD (Trotti and Bliwise, 2014), including for regional areas. In line with the literature, we found that the medication was the most commonly utilized sleep intervention reported (Roychowdhury and Forsyth, 2012). The likely reason for this is that sleep problems were primarily reported to medical practitioners who used sleep medication as a primary intervention (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…As previously noted, evidence-based sleep interventions are currently lacking for PD (Trotti and Bliwise, 2014), including for regional areas. In line with the literature, we found that the medication was the most commonly utilized sleep intervention reported (Roychowdhury and Forsyth, 2012). The likely reason for this is that sleep problems were primarily reported to medical practitioners who used sleep medication as a primary intervention (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Ambulatory HC clients with parkinsonism had a unique profile of risk factors compared to the other two groups in that relatively few risk factors were associated with falls. Moreover, wandering – a behaviour likely associated with co-morbid cognitive impairment, or behavioural sleep disorders common among people with PD (Roychowdhury & Forsyth, 2012; Thorpy, 2004) – was a predictor of falls only in those with parkinsonism. Interestingly, mild cognitive impairment but not co-morbid dementia diagnosis was associated with increased odds of falling in those with parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of sleeping disturbances and problems in Parkinson's disease is not yet well understood. Some researchers think that sleep disturbances are caused by difficulty with turning around (akinesia), difficulty with breathing and swallowing when sleeping, periodic limb movements or restless leg dyskinesia, muscle cramps, depression, anxiety, hallucinations, and pain (Roychowdhury & Forsyth, 2012).…”
Section: Cbt For Sleeping Disturbancesmentioning
confidence: 99%